Heritage As a Source of Studies into Industrial History: Using Digital Tools to Explore the Geography of the Industrialization - Esteban-Oliver, Guillermo; San José, Adrià; Martí-Henneberg, Jordi (Frontiers in Digital Humanities, 2017)
The main objective of this article is to explore the possibility of combining two very different sources in order to study the distribution of industrial activity throughout history. The traditional primary sources to use for this purpose are the official censuses on population and economic activity that have been conducted in the majority of countries since the mid-19th century. However, the majority of these lack detail at the regional level and also with respect to the types of professional occupations that they quantify. In order to complement and profile these census data, we propose the use of another type of information which can also be quantified, but whose characteristics are very different. We refer to the industrial heritage sites identified in digital format in a given territory, which in this case is Catalonia, Spain. This innovative dataset was obtained using digital tools like web scraping and data mining techniques.This type of historical information was used to check whether it is reliable and valid for interpreting the spatial impact of the introduction of industrial activity. The article also shows that the systematic identification of elements of industrial heritage offers a new and very useful source of information for interpreting the history of industrial geography.